Mismatch repair status in the prediction of benefit from adjuvant fluorouracil chemotherapy in colorectal cancer. Issue 6 (18th November 2005) - Jover, R; Zapater, P; Castells, A; Llor, X; Andreu, M; Cubiella, J; Piñol, V; Xicola, R M; Bujanda, L; Reñé, J M; Clofent, J; Bessa, X; et al.
Abstract : Aim: Some retrospective studies have shown a lack of benefit of 5-fluorouracil (5-FU) adjuvant chemotherapy in patients with mismatch repair (MMR) deficient colorectal cancer. Our aim was to assess if this molecular marker can predict benefit from 5-FU adjuvant chemotherapy. A second objective was to determine if MMR status influences short term survival. Methods: We included 754 patients with a median follow up of 728.5 days (range 1–1097). A total of 260 patients with stage II or III tumours received 5-FU adjuvant chemotherapy, according to standard clinical criteria and irrespective of their MMR status. A tumour was considered MMR deficient when either BAT-26 showed instability or there was loss of MLH1 or MSH2 protein expression. Results: At the end of the follow up period, 206 patients died and 120 presented with tumour recurrence. Sixty six (8.8%) patients had MMR deficient tumours. There were no significant differences in overall survival (MMR competent 72.1%; MMR deficient 78.8%; p = 0.3) or disease free survival (MMR competent 61.3%; MMR deficient 72.3%; p = 0.08). In patients with stage II and III tumours, benefit from 5-FU adjuvant chemotherapy was restricted to patients with MMR competent tumours (overall survival: chemotherapy 87.1%; non-chemotherapy 73.5%; log rank, p = 0.00001). Patients with MMR deficient tumours did not benefit from adjuvant chemotherapy (overall survival: chemotherapy 89.5%; non-chemotherapy 82.4%; log rank, p = 0.4). Conclusions: Benefit from 5-FU adjuvant chemotherapy depends on the MMR status of tumours in patients with colorectal cancer. 5-FU adjuvant chemotherapy improves survival in patients with MMR competent tumours but this benefit from chemotherapy cannot be extended to patients with MMR deficient tumours.